Low Power High Gain Op-Amp using Square Root based Current Generator (Global Journal of Computer Science and Technology, 2016)
A very high gain two stage CMOS operational amplifier has been presented The proposed circuit is implemented in 180nm CMOS technology with a supply voltage of 0 65V The current source in the OPAMP is replaced by a square root based current generator which helps to reduce the impact of process variations on the circuit and low power consumption due to the operation of MOS in subthreshold region So with the help of square root based current generator the better controllability over gain can be obtained The proposed opamp shows a high gain of 121 9dB and low power consumption of 11 89uW is achieved